PENGARUH MOTIVASI KERJA DAN KOMPETENSI GURU TERHADAP KINERJA GURU DIMODERASI KEPEMIMPINAN TRANSFORMASIONAL (Studi Kasus Pada Guru Madrasah Aliyah di Kecamatan Winong Kabupaten Pati) - Susilowati, Endah; Suhari, Yohanes (Jurnal Ilmiah Telaah Manajemen, 2016)
This study aims to examine and analyze whether the effect of work motivation and teacher competence on teacher performance is moderated by transformational leadership Principal for teacher of Madrasah Aliyah in Winong sub-districts of Pati regency.The numbers of data in this reseach is 83 (use sensus method). Multiple regression analysis is used to data analysis. The results showed that work motivation has positive effect on teachers performance, teachers competence has positive effect on teachers performance, transformational leadership has positive effect on teachers performance, the effect of work motivation on teachers performance is moderated by transformational leadership, and the effect of teachers competence on teachers’ performance is moderated by transformational leadership. Keywords: work motivation, teacher competence, transformational leadership, teacher performance